Analysis of the Process of Handing Over Housing Infrastructure, Facilities, and Utilities that have been Implemented in Indonesia - Agustini, Amanah Putri; Ningrum, Sinta; Zakaria, Zulfialdi (Universitas Muhammadiyah Gorontalo, 2024)
The goal of housing and settlement development is to create an environment and human living space that meets the essential needs of life, including security, protection, tranquility, self-development, health, beauty, and other necessities for the preservation of human life. The purpose of this study is to find out the policy of the process of handing over infrastructure, facilities, and housing utilities that have been implemented in areas in Indonesia. This study uses a case study method, namely by reviewing previous studies, to conclude. The results of the study show that there are several stages in the process of handing over housing infrastructure, facilities, and utilities in Indonesia, namely there is a stage of providing and developing infrastructure, facilities, and housing utilities, there is a stage of handing over housing infrastructure, facilities, and utilities from development to the district government, and finally there is a stage of registration or administration of housing infrastructure, facilities, and utilities. In addition, in the process of handing over, there are several weaknesses that are still faced by the local government in its policies, namely, location permits that are not recognized, weak law enforcement against housing developers, and the weakness of the housing monitoring team.